(untitled) (American Journal of Islam and Society, 1998)
S. Inati, translator. Ibn Sina and Mysticism: Remarks and Admonitions (Al-Isharat wa al-Tanbihat), Part Four. London and New York: Kegan Paul International, 1996, pp. 114. The book is an Fhglish translation and analysis of the fourth part of Ibn Sina’s Al-Isharat wa al-Tanbihat. This book “announces” a contribution to a specific aspect of Ibn Sina’s thought. Its main focus is the fourth part of his Al-Isharat wa al-Tanbihat (Remarks and Admonitions), which deals in a systematic manner with Islamic Sufism (mysticism), its different modifcations, and the kind of ternpod and transcendental experience that the soul undergoes in its journey back to its origin. Dr. S. Inati’s translation is the first into English of this part of the Isharat.’ It includes Ibn Sina’s dissertation in which he employs a form of descriptive psychology and scant aspects of his metaphysical system, as a focal point, to explain the drama of mystical life, its actualities, horizons, and pretensions. The Archimedean point of the Isharat is the experience of the Sufi (mystic) described in a crisp, vivid, and resonant Arabic. There is an excited, dynamic, and luminous simplicity in his style with sparse metaphors and practically no symbols or enigmas to hinder a direct comprehension of the themes discussed therein. Dr. Inati’s position on the Isharat is in harmony with the popularly held beliep that it is entirely a symbolic composition (pp. 2-3) which stands for or represents his othewise clear naturalistic doctrine? I disagree and shall defend this position later. The best part of this work is directly communicated, employing his conceptual categories as a device to illuminate the process of mystical gnosis. He must have believed that an appeal to his rational determinations from his cosmology and theory of the soul would provide models or “ideated structures” that enhance a better understanding of mysticism by himself and by his competent der. The Shaykh’s contribution in Isharut lies in his methd of description and inteptation and not in major novel themes about mysticism; the ...